An Analysis of Students’ Problem in Writing a Personal Letter at 11th Grade of MAN 4 Agam - Arnelia, Mutia Rahmi; Syahrul, Syahrul (Faculty of Education and Teacher Training of IAIN Palopo, 2021)
There were some students’ problems that the writer found at MAN 4 AGAM. First, some students could not develop their ideas when writing. Second, some students were confused about using tenses. Next, some students had limited vocabulary. The last, some students were wrong in diction. This research aimed to discover the students’ problems in writing personal letters and the causes of students’ problems in writing personal letters. In this research, the researcher used mix method by using descriptive design. The mixed-method was the combination of quantitative and qualitative research. The informants of this research were the students of the XI IS-1 class, which consisted of 19 students. The data were obtained through documentation and interview. This research found five aspects of students’ problems in writing a personal letter—the problems which percentage 18,2 % was content. The second was organization, with a percentage of 15,4 %. Next, the student's problem in grammar was 25,3 %. After that, the problem of vocabulary was 23,2 %. The last, mechanics’ problem was 17,7 %. Therefore, from the percentage, the most common of students’ problems was grammar. There were some causes why students got a problem in writing a personal letter. There was the psychological, linguistic, and cognitive problem. Thus, based on an interview with some students, the most cause of the problem was linguistic problems.